1997
DOI: 10.1002/bjs.1800841110
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic scoring systems to predict outcome in peritonitis and intra-abdominal sepsis

Abstract: Combination of the APACHE II and the MPI provides the best scoring system fitting clinical goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 15 publications
1
95
1
5
Order By: Relevance
“…Several risk scores exist for the prediction of outcomes in patients with perforated peptic ulcer. [8][9][10] Among the most frequently used are the ASA classification, the Boey score, MPI and the more recently introduced PULP score. However, only the Boey and PULP scores are specifically designed for the prediction of mortality in PPU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk scores exist for the prediction of outcomes in patients with perforated peptic ulcer. [8][9][10] Among the most frequently used are the ASA classification, the Boey score, MPI and the more recently introduced PULP score. However, only the Boey and PULP scores are specifically designed for the prediction of mortality in PPU patients.…”
Section: Discussionmentioning
confidence: 99%
“…P eritonitis continues to be one of the major abdominal emergencies causing high in-hospital morbidity and mortality rates up to 38% (1)(2)(3). Although the overall mortality of sepsis is ϳ35% (4), abdominal sepsis is associated with mortality rates up to 80% (5).…”
Section: Il-10-deficient Mice Demonstrate Multiple Organ Failure and mentioning
confidence: 99%
“…12 Although there were opinions that combination of APACHE II and MPI should be a standard classification system for grading severity of peritonitis and intra-abdominal sepsis. 13 Samir et al showed that MPI had no predictive power, while APACHE II does. 9 Organ failure is associated with prolonged stay and higher costs.…”
Section: Daysmentioning
confidence: 99%